2018
DOI: 10.14814/phy2.13683
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase (MMP)-7 in Barrett's esophagus and esophageal adenocarcinoma: expression, metabolism, and functional significance

Abstract: Matrix metalloproteinase (MMP)‐7, unlike many MMPs, is typically expressed in epithelial cells. It has been linked to epithelial responses to infection, injury, and tissue remodeling including the progression of a number of cancers. We have now examined how MMP‐7 expression changes in the progression to esophageal adenocarcinoma (EAC), and have studied mechanisms regulating its expression and its functional significance. Immunohistochemistry revealed that MMP‐7 was weakly expressed in normal squamous epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…MMPs are also biologically relevant for esophageal carcinogenesis. It has been previously shown that MMPs function as potential biomarkers, and distinct MMP subtypes, including MMP-1, MMP-2, MMP-3, MMP-7, and MMP-9, have been associated with EC diagnosis and/or prognosis [74][75][76][77][78][79]. In this way, among the nearly 30 distinct MMPs subtypes, MMP-2 and MMP-9 are the most strongly associated with esophageal carcinogenesis [74].…”
Section: Mmps and Ecm Remodelingmentioning
confidence: 93%
See 2 more Smart Citations
“…MMPs are also biologically relevant for esophageal carcinogenesis. It has been previously shown that MMPs function as potential biomarkers, and distinct MMP subtypes, including MMP-1, MMP-2, MMP-3, MMP-7, and MMP-9, have been associated with EC diagnosis and/or prognosis [74][75][76][77][78][79]. In this way, among the nearly 30 distinct MMPs subtypes, MMP-2 and MMP-9 are the most strongly associated with esophageal carcinogenesis [74].…”
Section: Mmps and Ecm Remodelingmentioning
confidence: 93%
“…Oppositely, the study performed by Garalla and colleagues showed that the blockage of the MAPK pathway was not able to interfere in MMP-7 expression [78], although MMP-7 aberrant levels had been previously related to EC progression [79,81]. Nonetheless, in the same study, the authors demonstrated that PI3K blockage, by using the chemical inhibitor LY294002, was able to strongly abolish MMP-7 secretion by EAC cells [78]. Additionally, the increase in MMP-7 levels could also be triggered through the modulation of other pathways, and, by using a panel of ESCC malignant cell lines, it was shown that the upregulation of AP-1 induced by activin A culminated with an increase in MMP-7 levels [82].…”
Section: Mmps and Ecm Remodelingmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that MMP-7 in BE epithelial cells could stimulate stromal cell migration and invasion and remodel the microenvironment under the regulation of PI3-K kinases. 30 In addition, MMP9 and MMP13 are also up-regulated in BE. 31 It is noteworthy that MMP13 is more highly expressed in BE, while MMP-9 is more highly expressed in EAC.…”
Section: Tumor Precursor Microenvironmentmentioning
confidence: 99%
“…The matrix metalloproteinases (MMPs) are a family of enzymes that digest components of the extracellular matrix (ECM) and are involved in cancer spreading and invasion [ 18 , 19 , 20 ]. Increases in MMP-1, MMP-2, MMP-7, MMP-9 and MMP-10 expression have all been linked to progression of normal oesophageal tissue to OAC [ 21 , 22 , 23 , 24 , 25 , 26 ] but the mechanism underlying what causes the increase in expression is currently unknown. It has been previously shown that BAs can promote MMPs that in turn enhance colon cancer invasion and metastasis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%